THE EFFECT OF SOCIAL MEDIA MARKETING AND ELECTRONIC WORD-OF-MOUTH ON HALAL FOOD PRODUCT PURCHASE DECISIONS - Herindar, Evania; Haidar, Abdullah (Khatulistiwa, 2024)
This study was inspired by the Covid-19 pandemic, particularly after the deployment of social distancing and work from home, which impacted the viability of MSME businesses. During this pandemic, social media has been predominantly used to market and promote products. However, greater research is required to determine the extent to which social media are effective as a product promotion and marketing technique. This study investigates the impact of social media marketing and electronic word-of-mouth on the decision to purchase halal food goods from MSMEs. Multiple linear regression analysis was employed in this study, with 154 respondents (generation Z) serving as the research sample obtained using stratified sampling with a significance threshold of 5%. 65.22% of the simultaneous test findings indicated that the two independent factors concurrently and partially had a positive and statistically significant effect on purchase decisions. In addition, this research employs literature reviews to propose creative marketing communication models through social media and marketing models using Instagram for small and medium-sized enterprises (SMEs).